Diagnostic Accuracy of Magnetic Resonance Cholangiopancreatography in the Detection of Choledocholith, taking Post-Operative findings as the Gold Standard - Javaid, Ayesha; Mahmood, Rashid; Ullah, Hidayat; Shafiq, Mazhar; Dildar, Nazia; Abbas, Ghulam (Pakistan Armed Forces Medical Journal, 2023)
Objective: To assess the diagnostic accuracy of Magnetic resonance cholangiopancreatography (MRCP) in the detection of Choledocholith, taking post-operative findings as the gold standard.Study Design: Cross-sectional validation studyPlace and Duration of Study: Combined Military Hospital, Kharian Pakistan, from Jan 2020 to Jan 2021.Methodology: Patients presenting with sonographic evidence of choledocholithiasis without any contraindications for magnetic resonance imaging were subjected to MRCP after informed consent. The patients who underwent surgery were followed up, and their per-operative findings were compared with the radiological findings of MRCP. Results: A total of 87 patients were included in the study. The mean age of patients was 37.04±10.49 years (range of 22-65 years). The sensitivity for MRCP was 95%, specificity was 73.33%, positive predictive value (PPV) was 93.44%, and negative predictive value was 78.57%. The diagnostic accuracy for MRCP was found to be 90.66%.Conclusion: The study shows that magnetic resonance cholangio-pancreatography is an effective imaging modality in diagnosing choledocholithiasis.